PENGEMBAGAN UNIT PEMBELAJARAN DENGAN SETTING FLIPPED CLASSROOM BERBASIS GUIDED INQUIRY MATERI SISTEM PEREDARAN DARAH - Sukur, Sri Irmayani; Ismail, Ismail; Patongai, Dian Dwi Putri Ulan Sari (Jurnal Biogenerasi, 2023)
In producing effective learning, a teacher needs learning tools that can support the learning process in the classroom. For this reason, teachers need learning tools in the form of teacher guidebooks to help the learning process, especially learning biology. This study aims to produce a learning unit with a flipped classroom learning setting based on guided inquiry on circulatory system material for class XI SMA/MA. This research is a development research that adapts the ADDIE development model which consists of analysis stages, namely needs analysis, content analysis, structure analysis, and objective analysis, the design stage is carried out by designing products consisting of cover design and content design, the development stage is tested for validity by an expert validator, the implementation stage is carried out by applying the product with practicality and effectiveness tests, and the evaluation stage is carried out by re-evaluating the product based on the practicality test. The developed learning unit is equipped with core competencies, basic competencies, learning materials, flipped classroom learning stages, guided inquiry learning scenarios, learning assessments, and student worksheets. The results showed practicality with an average score on the teacher and student response questionnaire, namely 86.6 and 84.02, included in the practical category.